Dis/value in co-production, co-design and co-innovation for individuals, groups and society - Sharon Williams (Public Money and Management, 2022)
Citizens may seek to co-create value during interactions with the provider (co-production), by contributing with improvements of existing services (co-design), or by inventing new services impacting the overall service system (co-innovation). Three empirical cases from Sweden and the UK suggest that disvalue is as likely an outcome as value creation, and that both outcomes need to be recognized at three levels: for the individual citizens themselves, their peer groups, and the broader society. The article contributes to the literature by questioning the assumption that value is inevitably created by theorizing and providing empirical cases that recognize disvalue to be an equally likely outcome in attempts to create value.